2006
DOI: 10.1143/jpsj.75.114716
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the Charge Ordering and Its Relevance to Superconductivity in θ-(BEDT-TTF)2X: The Effect of the Fermi Surface Nesting and the Distant Electron–Electron Interactions

Abstract: The origin of the charge ordering in organic compounds θ-(BEDT-TTF)2X (X = M M ′ (SCN)4, M =Tl,Rb,Co, M ′ =Cs,Zn) is studied using an extended Hubbard model. Calculating the charge susceptibility within random phase approximation (RPA), we find that the (3 × 3) ∼ (3 × 4) charge ordering observed at relatively high temperatures can be considered as a consequence of a cooperation between the Fermi surface nesting, controlled by the hopping integral in the c direction, and the electron-electron interactions, wher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 43 publications
2
57
0
Order By: Relevance
“…Moreover, even if the origin of the horizontal stripe in the Rb salt is the lattice distortion, the development of the horizontal stripe correlation at low temperatures in the Cs salt, where such a distortion has not been observed experimentally, remains puzzling. Related 9 to this point, Kuroki pointed out the possibility that the horizontal stripe charge correlation arises from the a-axis threefold correlation [30]. For the case of the Cs salt, although the nesting vector is close to (2/3, 1/3) f at high temperatures, it moves toward (3/4, 1/4) f (note that we are adopting the folded Brillouin zone scheme here) upon lowering the temperature as mentioned above.…”
Section: Future Problems Regarding the Competitionmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, even if the origin of the horizontal stripe in the Rb salt is the lattice distortion, the development of the horizontal stripe correlation at low temperatures in the Cs salt, where such a distortion has not been observed experimentally, remains puzzling. Related 9 to this point, Kuroki pointed out the possibility that the horizontal stripe charge correlation arises from the a-axis threefold correlation [30]. For the case of the Cs salt, although the nesting vector is close to (2/3, 1/3) f at high temperatures, it moves toward (3/4, 1/4) f (note that we are adopting the folded Brillouin zone scheme here) upon lowering the temperature as mentioned above.…”
Section: Future Problems Regarding the Competitionmentioning
confidence: 96%
“…There are several studies in which the pairing symmetry of superconductivity in X = I 3 has been discussed [28,30,33,43]. Since this superconductivity lies in the vicinity of the charge-ordering phase in Mori's electronic phase diagram (figure 1), one may expect the occurrence of unconventional superconductivity due to charge fluctuations.…”
Section: Future Problems Regarding the Competitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic phase diagram of this family has been composed employing the dihedral angle φ between the adjacent BEDT-TTF molecules (See Figure 9), which is related to the bandwidth [74]. The dihedral angle was subsequently linked to t c /t p to explain the phase diagram, where t c and t p are the transfer integrals along the c (stacking) direction and a ± c (diagonal) directions forming a triangular lattice [75][76][77][78]. Watanabe discussed this phase diagram using t c /t p as follows [78].…”
Section: θ-(Bedt-ttf) 2 Xmentioning
confidence: 99%
“…(a) IV characteristics of θ-ET 2 CsZn(SCN) 4 , adapted with permission from [83]; (b) Low temperature characters of the q 1 , q 1 and q 2 peaks of CsZn/Co and RbZn salts; (c) Time evolution of the X-ray intensities (peak and integrated ones) measured simultaneously with the resistivity, adapted with permission from [86], copyrighted by the Physical Society of Japan. Kuroki [89] made an attempt to explain the material-dependent wave numbers q 1 and q 1 (issue (3)) on the RPA basis, by introducing several extra V ij 's between those separated by two molecular spacing. He showed that the peak positions of the charge susceptibility χ c (q), which directly reflects the geometry of V (q) through W (q) in Equation (10), is sensitive in the chain direction, which reminds us of the degeneracy of chain stripes in the strong coupling theory.…”
Section: Competing Ordersmentioning
confidence: 99%